Modernity, State-Led Islamisation And The Non-Muslim Response : A Case Study Of Christians In Peninsular Malaysia - Chong , Eu Choong (2010)
For a better part of the 20th century, scholars who studied religion held the opinion that religion would gradually lose its public significance in the face of modernisation. However, events in the past few decades have proved otherwise. From the Iranian Revolution to the role of Catholicism in political conflicts throughout Latin America in the 1980 have patently demonstrated religion still plays an important role in the public sphere. This thesis takes the position that religion still remains an important precinct in the public life and politics of contemporary Southeast Asian societies. Using the case of Malaysia,